Java Quick Syntax Reference - Olsson, Mikael (Apress, 2018)
The Java 9 Quick Syntax Reference has been updated to now include aspects of Java 9 including modules, JShell and more. It is a condensed code and syntax reference to the Java programming language. It presents the essential Java syntax in a well-organized format that can be used as a handy reference. You won't find any technical jargon, bloated samples, drawn out history lessons or witty stories in this book. What you will find is a language reference that is concise, to the point and highly accessible. The book is packed with useful information and is a must-have for any Java programmer. What you'll learn: A concise reference to the Java 9 language syntax How to code with Java modules How to script with JShell How to box/unbox And more.